The Development of The Government’s Stimulus Model Policy on Harrod-Domar Economic Growth Model Relevant With Resources in Sulawesi Utara - Jeanne Rumawir (Journal of International Conference Proceedings (JICP), 2018)
This research aims at giving in-depth analysis the government’s stimulus model policy regarding the economic growth which favor poor society such as farmer, fishermen at the coastal area, and people at the slum area. This reseach applies developmental research method; the analysis model uses SEM (Structural Equation Modeling). Before applying this mdel, goodness of fit was conducted in order to find out whether this model can be accepted or not. The result of data analysis is goodness of fit; therefore, all variables can undergo further test. The test result shows that the changes in economic structures have direct influence on the government’s stimulus and economic growth which have significant values of 0,924 and 0,400 respectively. Capital establishment has direct effect on the government’s stimulus with the value of 0,051 which means that the influence is not significant. Capitall establishment has significant influence to the economic growth with the value of 0,223, and the socio cultural influence does not have significant influence to the economic growth with the value of 0,534. These results indicate that the greater stimulus of the government signified by precise goals leads to better economic growth. Keywords: Economic Growth, Government’s Stimulus Policy